2018
DOI: 10.1055/a-0586-8921
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Progression in Parents of Children with Cancer: Results of An Online Expert Survey in Pediatric Oncology

Abstract: Parental FoP is frequently perceived by experts in clinical practice. A standardized diagnostic procedure would increase comparability of diagnostic judgments and harmonize treatment indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Therefore, coping strategies offer some clinical implication in relation to FoP and a frequent use of helpful coping strategies can enhance the functional aspects of FoP (Dinkel, Henrich, & Herschbach, ). Addressing parents' coping strategies might thus be beneficial to reduce the negative consequences of dysfunctional parental FoP as experienced by healthcare professionals in pediatric oncology settings (Clever, Schepper, Küpper et al, ). Furthermore, our study provided evidence that coping is interpersonal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, coping strategies offer some clinical implication in relation to FoP and a frequent use of helpful coping strategies can enhance the functional aspects of FoP (Dinkel, Henrich, & Herschbach, ). Addressing parents' coping strategies might thus be beneficial to reduce the negative consequences of dysfunctional parental FoP as experienced by healthcare professionals in pediatric oncology settings (Clever, Schepper, Küpper et al, ). Furthermore, our study provided evidence that coping is interpersonal.…”
Section: Discussionmentioning
confidence: 99%
“…Although the manifestation of FoP is not necessarily associated with the objective risk of cancer recurrence, it is associated with illness cognitions, such as subjective risk perception (Koch et al, 2013;Simard et al, 2013). In an expert survey, professionals in pediatric oncology associated several negative consequences with parental FoP, for example, psychosomatic reactions, reduced family functioning, partnership problems, and overprotective behavior that could potentially hinder the child's social and academic reintegration after intensive treatment (Clever, Schepper, K€ upper, Christiansen, & Martini, 2018). Moreover, FoP might contribute to noncompliance or nonadherence to follow-up care recommendations (Best et al, 2001) as well as anxiety and depression in parents (Best et al, 2001;Ljungman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Significant gender differences in FoP levels of mothers and fathers could not be found, 12,14 nor was the child's age at diagnosis associated with parental FoP 12 . According to an expert online survey in Germany, health care professionals are frequently confronted with parental FoP in clinical practice 15 . Additionally, a recent interview study identified parental FoP as an impeding factor when reintegrating into daily life after the end of treatment 16 …”
Section: Introductionmentioning
confidence: 99%
“…12 According to an expert online survey in Germany, health care professionals are frequently confronted with parental FoP in clinical practice. 15 Additionally, a recent interview study identified parental FoP as an impeding factor when reintegrating into daily life after the end of treatment. 16 Overall, research on FoP of parents of childhood cancer survivors is still in its infancy.…”
mentioning
confidence: 99%
“…Difficulties in getting back to school could be due to a plethora of reasons like developing low self-esteem during the course of treatment, body image issues related to hair loss or surgery, sense of impending failure regarding competing with peers in academics and extra-curricular activities, shame related to the prospect of joining a class younger than his peers and parental anxiety in allowing the child to be back in school [48]. Many parents and young people are fearful that the cancer may come back and often get back to their oncologists even for minor health issues that are part of normal growing up [49]. Clinicians need to address these anxieties in a systemic way with the child and his or her family members.…”
Section: Helping Children To Get Back To Normal Life and Promoting Hementioning
confidence: 99%